СИСТЕМНАЯ КОНЦЕПЦИЯ ЭТИОЛОГИИ И ПАТОГЕНЕЗА ИШЕМИЧЕСКОЙ БОЛЕЗНИ СЕРДЦА. ОТДЕЛЬНЫЕ АСПЕКТЫ ЕЕ ЭТИОПАТОГЕНЕТИЧЕСКОЙ ДИАГНОСТИКИ, ПРОФИЛАКТИКИ И ЛЕЧЕНИЯ - В. С. Хазов (SINAPS LLC, 2015)
The IHD name doesn't completely reflect the disease essence. Its second name «coronary heart disease», that is widely spread in the west medicine, is even wronger. Systemic pathologists, cardiologists, that were one of the originators and their followers were mislead by the eye-catching coronary occlusion and the base method of the disease investigations, that was used then and used now - the method of the clinico-anatomical apposition (CAA). The described problem brought to the point that all the efforts taken by the scientists to the every possible heart circulation management didn't succeed. IHD incidence and mortality stay very high and in most of the countries keep increasing. System analysis, used instead of CAA gave an opportunity (according to this article's author) to find the real reason and this disease mechanism and to create a new system concept of the IHD matter. That will allow to change the approach to the disease and its cure cardinally.